An Explanatory and Predictive PLS-SEM approach to the Relationship between Product Involvement, Price and Brand Loyalty - Albert Albert; Felix Leonardi; Juliana Juliana; Arifin Djakasaputra (AGUSPATI RESEARCH INSTITUTA, 2022)
For customers, Price is an essential attribute and can be more important in decision making. Because when the customer is considering buying this product, Price may be a key element in the decision process. price can be an informational cue that increases customer sensitivity to private brands or brand loyalty. Likewise, consumer product involvement can increase brand loyalty. A company's success can be measured depending on its capability to attract customers to its brand. But, the manager of Asia Baru Shop – Medan, a grocery store for baby milk products, especially for Morinaga infant milk, found that today customers are hard to be loyal to a brand or specific brand because customers are sensitive to the price change, which has made the switch to other brands. This study aims to know the effect of Price on brand loyaltyand contribute to the literature on brand loyalty by demonstrating how product involvement influences brand loyaltyy. The sample of this research is 100 respondents who were distributed among Medan customers; the sampling technique uses simple random sampling. The authors used structural equation modeling to test the hypothesized model. This research is descriptive quantitative research. The result found that there is an effect of Price on brand loyalty and product involvement affects brand loyalty